Analysis Using Comsol Of Forced Convective Heat Transfer Past A Square Diamond Shaped Porous Cylinder - Asri, Aizat; Kamardan, Muhamad Ghazali (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates the forced convective heat transfer around a diamond-shaped porous cylinder by using COMSOL software. The dimensionless equations for mass, momentum, and energy were solved to produce streamlines and isotherms. By using a constant Darcy number (10-2 ) and changing the Reynolds number (Re), the analysis was conducted. The outcomes revealed that the effect on the cylinder was symmetrical at low Re with only a small distortion of the streamlines, meaning that the heat transfer was conduction dominated. As Re grows, the streamlines get stretched, and vortices occur downstream of the cylinder, thus telling us that the heat transfer has moved more to convection. The isotherms with an increased Re caused the thermal plume to become longer, this is a sign of the presence of inertial forces. The temperature at the cylinder surface remained high, though the heat was not the same at the points downstream. These results demonstrate the interaction of flow and heat transfer characteristics, and the finding is expected to be a source of knowledge regarding the forced convection in porous media.